Pengalaman Pembelajaran Transformatif Mahasiswa Keperawatan Selama Praktik Klinik: Studi Kualitatif Reflektif - Maria Julieta Esperanca Naibili (Universitas Malahayati, 2026)
ABSTRACT Clinical practice is a pivotal phase in nursing education and serves as a foundation for the formation of students’ professional identity. However, this phase is often accompanied by emotional tension, adaptation challenges, and complex learning dynamics that influence students’ readiness and personal transformation. This study aimed to explore the process of self-transformation among nursing students through their first clinical practice experience. A reflective qualitative design was employed, involving 34 undergraduate nursing students from classes IA and IC at the University of Timor (UNIMOR) who completed their initial clinical practice for the Fundamentals of Nursing course at Mgr. Gabriel Manek, SVD Hospital, Atambua, from 5 May to 28 June 2025. Data were obtained from in-depth written reflections and analyzed using reflective thematic analysis to identify patterns of personal and professional change. Four major themes emerged: (1) emotional transition from fear to confidence; (2) reframing the role and responsibilities of professional nurses; (3) strengthening communication skills, empathy, and self-regulation; and (4) professional identity formation through continuous reflection. Findings indicate that clinical practice plays a substantial role in shaping students’ emotional, ethical, and professional competencies. Clinical practice strengthens not only students’ technical abilities but also serves as a crucial space for personal transformation and the development of professional identity. Educational institutions are encouraged to enhance reflective support and emotional guidance to facilitate student growth during clinical placements. Keywords: Self-Transformation, Clinical Practice, Nursing Students, Reflection, Professional Identity. ABSTRAK Pengalaman praktik klinik merupakan fase fundamental dalam pendidikan keperawatan dan menjadi landasan pembentukan identitas profesional mahasiswa. Namun, fase ini sering disertai ketegangan emosional, tuntutan adaptasi, dan dinamika pembelajaran yang kompleks yang dapat memengaruhi kesiapan dan proses transformasi diri mahasiswa. Penelitian ini bertujuan mengeksplorasi proses transformasi diri mahasiswa keperawatan melalui pengalaman praktik klinik pertama. Penelitian menggunakan desain kualitatif reflektif dengan melibatkan 34 mahasiswa Program Studi Keperawatan UNIMOR dari kelas IA dan IC yang telah menyelesaikan praktik klinik perdana pada mata kuliah Keperawatan Dasar di RSUD Mgr. Gabriel Manek, SVD Atambua, periode 5 Mei–28 Juni 2025. Data dikumpulkan melalui refleksi tertulis mendalam dan dianalisis menggunakan analisis tematik reflektif untuk mengidentifikasi pola perubahan personal dan profesional selama praktik. Empat tema utama ditemukan, yaitu: (1) transisi emosional dari ketakutan menuju kepercayaan diri; (2) pemaknaan ulang peran dan tanggung jawab profesional perawat; (3) penguatan keterampilan komunikasi, empati, dan regulasi diri; dan (4) pembentukan identitas profesional melalui refleksi berkelanjutan. Temuan menunjukkan bahwa praktik klinik berperan signifikan dalam pengembangan kompetensi emosional, etis, dan profesional mahasiswa. Praktik klinik tidak hanya memperkuat keterampilan teknis, tetapi juga menjadi ruang penting bagi transformasi personal dan pembentukan identitas profesional mahasiswa keperawatan. Institusi pendidikan perlu memperkuat dukungan reflektif dan pembinaan emosional untuk memfasilitasi perkembangan mahasiswa selama praktik klinik. Kata Kunci: Transformasi Diri, Praktik Klinik, Mahasiswa Keperawatan, Refleksi, Identitas Profesional.